Chapter 13 Nordic Literary Translingualism - Hansen, Julie (Taylor & Francis, 2022)
This chapter surveys the diverse landscape of literary translingualism in the Nordic region. A brief overview of contemporary language situations in the Nordic countries is followed by an examination of translingual aspects of the work of Henrik Ibsen, August Strindberg, Edith Södergran, Karen Blixen, and Kjartan Fløgstad. The subsequent sections discuss trends in Nordic literary translingualism from the late twentieth and early twenty-first centuries, focusing in particular on postcolonial contexts, minority literatures, and migration. The chapter concludes with a consideration of how works by Tomas Tranströmer, Caroline Bergvall, and Cia Rinne invite translingual readings.